THE INFLUENCE OF MOTIVATION, JOB SATISFACTION, AND DISCIPLINE WORK ON EMPLOYEE PERFORMANCE IN PT. GLOBAL PENTA BRANCH RESTAURANT XO SUKI MEDAN - Gabriella Awina Sinurat; Novmeri Halawa; Tantia Irani; Dinda Aida Fitri; Maya Agustina Tanjung (Jurnal Ekonomi, 2022)
Motivation, job happiness, and work discipline may all influence an employee's performance. The goal of this study is to investigate and analyze the influence that employees of PT. Benua Penta Global's motivation, job happiness, and work discipline have on the performance of those employees, the XO Suki restaurant's Medan location. This is an illustration of explicative research. The research population will consist of all 112 workers that worked at PT Benua Penta Global's restaurant branch XO Suki Medan from January to December 2021. Due to the limited population size of 112 employees, the Slovin sampling technique will be used to get up to 88 respondents to whom Likert scale-based questionnaires will be distributed. In order to analyze the data, we used simultaneous and partial tests, as well as multiple linear regression and the coefficient of determination. PT performance was significantly improved by motivation, job satisfaction, and work discipline. This finding was supported by statistical analysis. Benua Penta Global, the Medan location of XO Suki restaurant. The findings of this study indicate that management should strive to enhance employee motivation, job satisfaction, and workplace discipline.